Nondestructive monitoring storage quality of apples at different temperatures by near‐infrared transmittance spectroscopy. Issue 7 (27th May 2020) - Guo, Zhiming; Wang, Mingming; Shujat, Ali; Wu, Jingzhu; El‐Seedi, Hesham R.; Shi, Jiyong; Ouyang, Qin; Chen, Quansheng; Zou, Xiaobo
Abstract: Apple is the most widely planted fruit in the world and is popular in consumers because of its rich nutritional value. In this study, the portable near‐infrared (NIR) transmittance spectroscopy coupled with temperature compensation and chemometric algorithms was applied to detect the storage quality of apples. The postharvest quality of apples including soluble solids content (SSC), vitamin C (VC), titratable acid (TA), and firmness was evaluated, and the portable spectrometer was used to obtain near‐infrared transmittance spectra of apples in the wavelength range of 590–1, 200 nm. Mixed temperature compensation method (MTC) was used to reduce the influence of temperature on the models and to improve the adaptability of the models. Then, variable selection methods, such as uninformative variable elimination (UVE), competitive adaptive reweighted sampling (CARS), and successive projections algorithm (SPA), were developed to improve the performance of the models by determining characteristic variables and reducing redundancy. Comparing the full spectral models with the models established on variables selected by different variable selection methods, the CARS combined with partial least squares (PLS) showed the best performance with prediction correlation coefficient ( R p ) and residual predictive deviation (RPD) values of 0.9236, 2.604 for SSC; 0.8684, 2.002 for TA; 0.8922, 2.087 for VC; and 0.8207, 1.992 for firmness, respectively. Results showed that NIR transmittance spectroscopy was feasible to detect postharvest quality of apples during storage. Abstract : Near‐infrared transmittance spectroscopy coupled with temperature compensation and chemometric algorithms was applied to detect the storage quality of apples. Results showed that near‐infrared transmittance spectroscopy was feasible to detect postharvest quality of apples during storage.